2020
DOI: 10.3390/vaccines8040617
|View full text |Cite
|
Sign up to set email alerts
|

IFN-Alpha-Mediated Differentiation of Dendritic Cells for Cancer Immunotherapy: Advances and Perspectives

Abstract: The past decade has seen tremendous developments in novel cancer therapies through targeting immune-checkpoint molecules. However, since increasing the presentation of tumor antigens remains one of the major issues for eliciting a strong antitumor immune response, dendritic cells (DC) still hold a great potential for the development of cancer immunotherapy. A considerable body of evidence clearly demonstrates the importance of the interactions of type I IFN with the immune system for the generation of a durabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 82 publications
(119 reference statements)
0
16
0
1
Order By: Relevance
“…It was shown pre-clinically that monocytes modified to express IFN-α reprogrammed the tumor microenvironment and inhibited leukemia in a mouse model. 31 We and others 32 have shown that IFN-α promotes the ex vivo differentiation of mature DCs with migratory capabilities, and therefore, IFN-DCs are actively being exploited in clinical trials for cancer vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown pre-clinically that monocytes modified to express IFN-α reprogrammed the tumor microenvironment and inhibited leukemia in a mouse model. 31 We and others 32 have shown that IFN-α promotes the ex vivo differentiation of mature DCs with migratory capabilities, and therefore, IFN-DCs are actively being exploited in clinical trials for cancer vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-α is well known for its key roles in antiviral immune responses. Recently, the intratumoral expression levels of IFN-α and IFIT genes were reported to be associated with improved patient outcomes in multiple cohorts of cancer cases, and new anticancer immunotherapies based on recombinant IFN-α have been recently developed [37][38][39]. Therefore, our ndings further con rmed TIM-1 as a potential biomarker of BC that could regulate IFIT2 and intratumoral IFN-α, playing a dual antitumor role due to the important role of the cytokine IFN-α in tumor immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…59 Surprisingly, in the absence of maturation factors, fully functional IFN-DCs can be differentiated after 3 days of culture, thus facilitating clinical applications. 58 However, upon inoculation with different antigens, the advantages of IL-4 MoDCs and IFN-DCs differ. In the context of DC vaccination with synthetic long peptide (SLP), the use of IFN-DCs is superior to IL-4 MoDCs, whereas IL-4 MoDCs are more suitable for vaccination with antigens from apoptotic cellderived blebs.…”
Section: Dc-based Cancer Vaccinesmentioning
confidence: 99%